The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Library science text series, 1987)
Keywords: School libraries; dept.ils; faculty_collection

Output measures and library space planning - Lushington, N. (Library Trends, 1987)
This article suggests that over the next decade library performance measures - such as output measures - can become the basis for library space planning programs that will determine the quantity and relative location of user hierarchies for each type of public service.
Keywords: dept.ils; ⛔ No DOI found